ANALISIS KEBOCORAN SAMBUNGAN REGULATOR TABUNG SCBA (SELF-CONTAINED BREATHING APPARATUS) UNTUK MENINGKATKAN KESELAMATAN AWAK KAPAL DI KM. SIRIMAU - Yulandani; Bayu Yudho Baskoro; Rizal Rochmansyah; Elfira Wirza; Tri Kismantoro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
YULANDANI, NIT: 113307221039, 2026, “Analysis of Leakage in SCBA (Self-Contained Breathing Apparatus) Cylinder Regulator Connections to Improve Crew Safety on KM. Sirimau”. Supervised by Bayu Yudho Baskoro, S.S.T.Pel., M.Pd. and Elfira Wirza, S.Si., M.Sc.This study aims to identify the factors causing leakage in the regulator connection of the Self-Contained Breathing Apparatus (SCBA) cylinder and to analyze its impact on the safety of crew members aboard KM. Sirimau. SCBA is an essential safety device used by crew members during emergency situations, such as fires and exposure to toxic smoke, so its condition and reliability must always be maintained.This research employed a qualitative descriptive method with data collection techniques consisting of observation, interviews, and documentation. The research informants were the Chief Officer, Third Officer, and Bosun, who were directly involved in the use and maintenance of SCBA on board. Data were analyzed through data reduction, data presentation, and conclusion drawing.The results show that leakage in the SCBA regulator connection was caused by gaps between the regulator and cylinder connection, inadequate inspection and maintenance practices, and operational errors. Such leakage reduces air supply, decreases SCBA performance, and increases safety risks for crew members during emergencies. Efforts to minimize these risks include routine inspections, maintenance according to established procedures, improved SCBA usage training, and stricter supervision of safety equipment conditions.